2022
DOI: 10.3390/mi13071025
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancement in Optical Metasurface: Fundament to Application

Abstract: Metasurfaces have gained growing interest in recent years due to their simplicity in manufacturing and lower insertion losses. Meanwhile, they can provide unprecedented control over the spatial distribution of transmitted and reflected optical fields in a compact form. The metasurfaces are a kind of planar array of resonant subwavelength components that, depending on the intended optical wavefronts to be sculpted, can be strictly periodic or quasi-periodic, or even aperiodic. For instance, gradient metasurface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 144 publications
0
12
0
Order By: Relevance
“…Moreover, nanostructure-paint through DNA allows the fabrication of planar optical metasurfaces, arrays of microscopic light scatterers, whose overall optical properties emerge from microscale structures, as it can be observed in the structural color of a butterfly wing [ 248 , 249 ]. Due to the excellent control over light, metasurfaces are typically envisioned for use in large-area applications such as windows and solar cells, functional coatings, holograms, wavefront shaping, and structural color printing [ 3 , 250 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%
“…Moreover, nanostructure-paint through DNA allows the fabrication of planar optical metasurfaces, arrays of microscopic light scatterers, whose overall optical properties emerge from microscale structures, as it can be observed in the structural color of a butterfly wing [ 248 , 249 ]. Due to the excellent control over light, metasurfaces are typically envisioned for use in large-area applications such as windows and solar cells, functional coatings, holograms, wavefront shaping, and structural color printing [ 3 , 250 ].…”
Section: Dna/rna Based Metamaterialsmentioning
confidence: 99%
“…The metasurface is highly efficient in acquiring low-profile, high-efficiency, and broadband polarization converters [ 8 ]. Polarization converters have distinct properties in controlling polarization and they have been utilized in the microwave [ 9 ], terahertz [ 10 ], and even optical [ 11 ] range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces attain a considerable attention in military stealth due to low profile and strong electromagnetic (EM) wave manipulation abilities [ 9 , 10 , 11 ]. They can easily control the amplitude, polarization, and phase of EM waves [ 12 , 13 , 14 ]. Recently, it has been observed that metasurfaces have extensively been used to perform absorption and scattering.…”
Section: Introductionmentioning
confidence: 99%